Pelatihan Penyusunan Proposal Classroom Based Action Research bagi Guru Sekolah Dasar - Via Yustitia; Triman Juniarso; Bahauddin Azmy; Cholifah Tur Rosidah; Bramianto Setiawan (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON CLASSROOM BASED ACTION RESEARCH PROPOSAL DEVELOPMENT FOR ELEMENTARY SCHOOL TEACHERS. Classroom Based Action Research is a demand for elementary school teachers. Most teachers find it difficult to plan classroom action research. The PKM aims to: (1) improve the understanding of SDN Gayungan 2 teachers about planning; (2) increase the ability of teachers in planning. These PKM partners are teachers at Sidayu district. The method used in the service activities is the lecture and demonstration methods. Overall service activities can be judged to be quite good, seen from the success of the target number of trainees considered to be quite good, the achievement of training objectives is considered not good, the achievement of planned material targets is considered good, and the ability of participants in mastering the material is considered good.